Host Cell Specificity of Minute Virus of Mice in the Developing Mouse Embryo - Itah, Refael (American Society for Microbiology, 2004)
Productive infection by the murine autonomous parvovirus minute virus of mice (MVM) depends on a dividing cell population and its differentiation state. We have extended the in vivo analysis of the MVM host cell type range into the developing embryo by in utero inoculation followed by further gestation. The fibrotropic p strain (MVMp) and the lymphotropic i strain (MVMi) did not productively infect the early mouse embryo but were able to infect overlapping sets of cell types in the mid- or late-gestation embryo. Both MVMp and MVMi infected developing bone primordia, notochord, central nervous system, and dorsal root ganglia. MVMp exhibited extensive infection in fibroblasts, in the epithelia of lung and developing nose, and, to a lesser extent, in the gut. MVMi also infected endothelium. The data indicated that the host ranges of the two MVM strains consist of overlapping sets of cell types that are broader than previously known from neonate and in vitro infection experiments. The correlation between MVM host cell types and the cell types that activate the transgenic P4 promoter is consistent with the hypothesis that activation of the incoming viral P4 promoter by the host cell is one of the host range determinants of MVM.